Resilience to Freezing in the Vegetative Cells of the Microalga Lobosphaera incisa (Trebouxiophyceae, Chlorophyta). Issue 2 (3rd January 2020) - Kugler, Amit; Kumari, Puja; Kokabi, Kamilya; Itkin, Maxim; Malitsky, Sergey; Khozin‐Goldberg, Inna
Abstract : The chlorophyte microalga Lobosphaera incisa was isolated from the snowy slopes of Mt. Tateyama in Japan. This microalga stores exceptionally high amounts of the omega‐6 LC‐PUFA arachidonic acid in triacylglycerols, and therefore represents a potent photosynthetic source for this essential LC‐PUFA. Assuming that freezing tolerance may play a role in adaptation of L. incisa to specific ecological niches, we examined the capability of L. incisa to tolerate extreme sub‐zero temperatures. We report here, that the vegetative cells of L. incisa survived freezing at −20°C and −80°C (over 1 month), without cryoprotective agents or prior treatments. Cells successfully recovered upon thawing and proliferated under optimal growth conditions (25°C). However, cells frozen at −80°C showed better recovery and lower cellular ROS generation upon thawing, compared to those preserved at −20°C. Photosynthetic yield of PSII, estimated by F v / F m, temporarily decreased at day 1 post freezing and resumed to the original level at day 3. Interestingly, the thawed algal cultures produced a higher level of chlorophylls, exceeding the control culture. The polar metabolome of the vegetative cells comprised a range of compatible solutes, dominated by glutamate, sucrose, and proline. We posit that the presence of endogenous cryoprotectants, a rigid multilayer cell wall, the high LC‐PUFA content in membrane lipids, and putative cold‐responsive proteins may contribute to the retention of functionality upon recovery from the frozen state, and therefore for the survival under cryospheric conditions. From the applied perspective, this beneficial property holds promise for the cryopreservation of starter cultures for research and commercial purposes.